Abiotic factors involved in wheat tolerance to frost - Silva, Eunice Portela da; Cunha, Gilberto Rocca da; Pires, João Leonardo Fernandes; Dalmago, Genei Antonio; Pasinato, Aldemir (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this work was to evaluate the influence of acclimatization, frost intensity and soil water availability on damage caused by frost on wheat. The experiments were carried out in screen house conditions. The wheat plants were grown in pots. The acclimatization and frost incidence were simulated in a growth chamber. The abiotic factors evaluated were: acclimatization regimes (with and without); temperature gradient (2, -2, -4 and -7°C) and variation of soil water availability prior to frost incidence (9, 6, 3 and 1 day without irrigation). All factors were evaluated at tillering, stem elongation and heading stage on wheat cultivars BR-18 Terena, more tolerant to frost, and BRS 194, less tolerant. The response variables were: degree of leaf scorching symptoms at 7 days after frost; total dry weight; and grain weight. The acclimatization, before frost, decreased the damage caused on wheat heading stage, which resulted in less leaf scorching symptoms and higher grain yield. Temperature of -7°C, at heading stage, resulted in grain set failure in both cultivars; and frost damage was lower in plants with nine days without irrigation. Prevailing conditions before frost influence frost damage.